2002
DOI: 10.1002/cncr.10666
|View full text |Cite
|
Sign up to set email alerts
|

Calbindin‐D28k

Abstract: BACKGROUNDThe expression of the Ca2+‐binding protein calbindin‐D28k was analyzed in medulloblastomas in relation to clinical features and other biologic markers related to cell proliferation, differentiation, p53, and cerebellar developmental regulated gene expression.METHODSImmunohistochemistry was carried out on histologic slides from a first retrospective series of 29 nonmetastatic and 10 metastatic medulloblastoma formalin‐fixed, paraffin‐embedded tissues, using specific antibodies against calbindin‐D28k, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…33 Although most human adult tissues do not express CALB1 , its ectopic expression has been observed in several cancer types. 34,35 Recent functional studies have demonstrated a novel oncogenic activity of CALB1 where it binds MDM2 to enhance MDM2-mediated suppression of p53 signaling. 34 This is especially important in the context of DD-LPS, as MDM2 overexpression, leading to p53 degradation, is a hallmark of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…33 Although most human adult tissues do not express CALB1 , its ectopic expression has been observed in several cancer types. 34,35 Recent functional studies have demonstrated a novel oncogenic activity of CALB1 where it binds MDM2 to enhance MDM2-mediated suppression of p53 signaling. 34 This is especially important in the context of DD-LPS, as MDM2 overexpression, leading to p53 degradation, is a hallmark of this disease.…”
Section: Discussionmentioning
confidence: 99%